부패조와 호기성 여과공정을 이용한 영양염류 제거 - 박상민; Sang Min Park; 전항배; Hang Bae Jun; 배종훈; Jong Hun Bae; 박우균; Woo Kyun Park; 박노백; Noh Back Park (Hanguk hwangyeong nonghak hoeji, 2010)
본 연구에서는 UST-AF 시스템에 전(前)응집 후(後)생물학적 처리 공정을 도입하여 질소와 인을 동시에 제거하고자 하였다. 연속공정은 유기물 및 SS의 제거 효율이 90%이상으로 균등화 효과와 질산화 효율이 높았다. 호기성 여과조에서 질산화 효율이 95% 이상이었으며, 반송을 통한 탈질화 효율은 80% 이상이었다. 하수원수에 화학적 처리 공정을 도입하여 총인을 90% 이상 제거하였으며, 후속공정의 생물반응에 영향을 주지 않은 alum 주입량은 40 mg/L이었다. 그러나 하수원수에 포함된 응집제에 의한 생물반응의 저해는 관찰되지 않았으나, 향후 장기간 운전하였을 경우 공정내 축적된 응집 슬러지의 영향에 대한 고찰이 필요할 것으로 예상된다. The objective of this study was to investigate a small sewage treatment system. This system was developed to improve a nitrogen and phosphorus removal efficiency and generate less solid using upflow septic tank(UST)-aerobic filter(AF) system. The UST equipped with an aerobic filter, the filter was fed with both raw sewage and recycled effluent from the UST to induce the denitrification and solid reduction simultaneously. Overall removal efficiencies of COD and total nitrogen(TN) were above 96% and 73% at recycle ratio of 200%, respectively. Critical coagulant dose without the biochemical activity was found to be 40 mg/L. Removal efficiency of total phosphorus(TP) in influent was above 90% by chemical and biological reactions. Although the phosphorus concentration was low under the high alkalinity in raw sewage, the pH value was unchanged by the coagulant dose.